Effects of beating on the characteristics of Malaysian durian (Durio Zibethinus Murr.) rind chemi-mechanical (CMP) pulp and paper - Masrol, Shaiful Rizal; Irwan Ibrahim, Mohd Halim; Adnan, Sharmiza; Ahmad Tajudin, Muhammad Syauqi Asyraf; Raub, Radhi Abdul; Abdul Razak, Siti Nurul Aqma; Md Zain, Siti Nur Faeza (Penerbit UTM Press, 2017)
The effects of beating on the characteristics of pulp and paper derived from durian rind under chemi-mechanical pulping (CMP) method were investigated. All process and characteristic tests were conducted according to Malaysian International Organization for Standardization (MS ISO) and Technical Association of the Pulp and Paper Industry (TAPPI). The unbeaten durian rind CMP pulp (control pulp) was beaten by using PFI mill at three (3) different beating levels; 1000, 2000 and 3000 revolutions. It was found that durian rind CMP pulp drainage time was increased (longer time) and freeness level was decreased as the beating revolutions were increased compared to the control pulp. The result shows that paper bulk density and overall mechanical characteristics (tensile index, tear index, burst index and folding no.) of 60 gsm durian rind CMP hand sheets were increased with the increment of beating revolutions.